Acid Suppressant Activity of Feed Dietary Supplements for Dogs: An In vitro Study - Bruni, Natascia; Martello, Elisa; Gabriele, Valeria; Perondi, Francesca (Journal of Pharmacy and Nutrition Sciences, 2023)
Gastritis is a common finding in pets and acid suppression plays an important role in its management. Acid suppression is the most important component in the treatment of gastritis and prevention of its complications. There are many drugs commonly used in veterinary medicine but the use of natural feed supplements is increasing. The aim of this in vitro study is the comparison of four supplements based on a combination of antacid salts and natural products at two pH conditions (pH 2 and 4.5) and at five time points. In addition, we wanted to confirm the formation of the gel during the test. All the products demonstrated acid suppression activity. In particular, product A showed the best performance. All the products except one (product B) formed gel after five minutes from the beginning of the experiment confirming their protective activity. Based on this preliminary results, the product A resulted to be the most promising antacid and potentially gastric protective product compared to others.